Evaluation of Straw Flax Preparation Quality in the Framework of Separate Flax Harvesting Technology - I. V. Sizov; L. N. Pak; E. S. Belyakova (Сельскохозяйственные машины и технологии, 2023)
The paper explores the technological aspects and methods involved in the preparation of flax straw within the framework of separate fiber flax harvesting technology. This particular technology allows for the prolonged maturation of seeds in the field. The study demonstrates that during the process of seasoning flax straw in the form of unprocessed stem ribbons, the seeds within the capsules undergo natural drying and ripening. This approach enables a reduction in fuel consumption compared to the traditional scheme while obtaining high-quality fiber and seeds suitable for sowing. (Research purpose) The objective of this study is to assess the quality of raw flax during the stage of straw flax preparation. (Materials and methods) The study investigates the processes and technical units involved in fiber flax harvesting, adhering to regulatory guidelines during the stages of stem pulling, seasoning, turning, picking, and processing are thoroughly examined. (Results and discussion) The research results have revealed the indicators for biological productivity of straw and seeds during the process of straw flax preparation. Under different seeding rates, the yield of straw flax ranges from 23.1 to 24.8 centners per hectare during a 14-day seasoning period and from 20.8 to 22.2 centners per hectare on the 21st day. These findings demonstrate that the average yield under various harvesting conditions is 20-30 centners per hectare. The flaxseed yield, ranging from 2.9 to 4.1 centners per hectare at different maturation periods, can be considered satisfactory. Furthermore, it was observed that the elongation of the flax ribbon increases after turning, compared to its initial state, when the combine speed is 5.3 and 7.8 kilometers per hour, remaining within the acceptable limits. However, at a speed of 9.6 kilometers per hour, there was a violation of agrotechnical requirements. (Conclusions) The separate harvesting of flax has proven to be effective during a three-week period of raw flax seasoning. It is important to note that when turning unprocessed flax ribbons, the working speed should not exceed 9 kilometers per hour.